Analysis and Design of Waste Management System for Engineering Industry - Singh, Tejinder Paul (My University, 2007)
Industry has been recognised to be the largest single consumer of finite natural resources. Rapid depletion of natural resources and consequential rise in their price has to be absorbed largely by the industry itself. High competition in the free market does not permit the transfer of resultant increase in the cost of production to consumers. Industry is, therefore, hard pressed to exploit all the engineering, technological and managerial skills to reduce manufacturing costs. Judicious selection of resources and their efficient utilisation should surely help a lot in achieving the defined objective through mitigation or atleast substantial reduction of wastages of all kinds. Waste is visualised as any unnecessary input to or any undesirable output from a system. Waste can occur in variety of forms and at number of stages in an engineering industry. Besides the scrap produced and undesirable outcomes of the processes, there are other forms of waste such as using more expensive materials than required, consuming excessive energy, using old technology, keeping higher inventories, under-utilisation of machinery and manpower and so on. Concerted and sustained efforts alone using appropriate technology at every stage of production activity can check waste generation. In the given situation, waste management programme gains importance. For an effective management approach, it is prudent to deal with waste at a system level. Despite the industry being alive to the prevailing dismal situation it is continuing with the old practices or have marginally improved. It is largely due to lack of awareness and familiarity on the part of the industry, with the tools and techniques of waste management and their application in the real life situations. Accordingly, industry is not in a position to precisely work out the amount of waste being generated and effectively mitigate it. To facilitate adoption of WM practices by an industry, it is desirable to make available in an easily useable form all the requisite information regarding tools and techniques, their applications and effects. This study has been undertaken with the objective of analysing all aspects of waste in the engineering industry and formulating a WM system for its use. The study has been divided into two parts: Analysis and Design. The work has been carried out in four phases: Survey on waste management; case studies; mathematical modelling and formulation of the WM system. A detailed survey on various aspects of waste management has been chosen as a means to analyse the industrial systems in general. For more detailed analysis, case (ix)studies in each resource area of materials, energy, capital and manpower using mathematical modelling has been carried out. The survey has been conducted through a specially designed questionnaire and status of various industries with regard to waste management as well as the state of various aspects of use of resources in various industries have been found out. Case studies have been conducted in an identified industry to find out areas and quantums of waste at various stages, their reasons and root causes and to generate alternate solutions. The system has been divided into various identifiable sub-systems and input-output analysis of 'materials' conducted for each sub- system. The amount of waste generated at each stage has been identified along with the probable reasons causing waste. Methods to mitigate waste have been listed. In the 'case study' on 'energy'the difference of actual energy comsumption and the ideal energy consumption of various sub-systems has been worked out to calculate waste. Reasons of waste caused and possible solutions for their mitigation are listed. Various areas analysed using appropriate techniques in 'capital' resource are: machine and plant utilisation; under-utilisation of machines with respect to sizes of the processed jobs; calculating waste due to difference between actual capacity and targetted capacity; inventory levels and state of automation. Case study on 'manpower' involves critical analysis to find out human error responsible for the wastage of resources of materials, energy and capital. Further, wastage of manpower itself due to overstaffing, overtimes, skill levels, and strikes, lockouts and disputes, etc. has been worked out. Physical system theory model has been used for representing case situation in materials. For energy PST has been used in two phases. Due to multi-objectivity, involved, goal programming model has been used for capital. In manpower, a qualitative model using OFM (Options Field Methodology), AHP (Analytical Hierarchy Process) and FST (Fuzzy Set Theory) has been applied. Broad outcomes of the survey, case studies and modelling have been listed, conclusions drawn and synthesised. Based on this information and the literature available, The WM system has been formulated. For deciding upon the format of the system, expert . . . . opinion of the industry has been sought and duly incorporated. The WM system is in the form of a manual and can be referred to for both general guidelines as well as specific problems at various stages of the plant life. The system enlists various areas of waste in each resource, provides checklist (x) of reasons of waste and recommends a number of alternate solutions for waste management. The study, by exposing areas of waste in each resource, their reasons and mitigation has served twin purposes of generating large data base on waste management practices and design of generalised guidelines, in the form of a WM system. Areas needing more detailed studies at micro level have been exposed. There is an ample scope to further explore these areas as well as extention of this study to process industry and also to other sectors like municipal, domestic and agricultural.
Keywords: Waste Management; Manufacturing; Mechanical Engineering